Knowledge, Key Motivation and Obstacles to Become COVID-19 Convalescent Plasma Donor among Medical Students of Rawalpindi Medical University, Pakistan: A Cross-Sectional Study - Hassan Jamal; Hafsa saddiqa; Sohaib Roomi; Umaira Ali; Bilal Khalid; Rabia Rafique; Syed Saqib Ali Shah (Students' Supplement of Journal of Rawalpindi Medical College, 2022)
Background: Gaining convalescent plasma from individuals recuperated from COVID-19 with adequate immune response titers is a possible choice for the treatment and anticipation of COVID-19. Objective: To determine the knowledge, key motivations of donating and causes of not donating convalescent plasma by qualified donors. Materials and Methods: It is an analytical cross-sectional study. A sample of 347 was collected using the convenience sampling technique. Respondents were asked to fill out questionnaires about their understanding of convalescent plasma, their motives, and hurdles to donation. MBBS students of Rawalpindi medical university were included while students with any chronic disease, COVID-19 infection, immunosuppression, blood-borne diseases, leukemic, thalassemic, and smokers were excluded. Comparative analysis was done using independent T-test and linear regression was applied. Results: Participants were predominantly females 222 in number (61%) and 57% of respondents were aged between 20-22 years. Knowledge of convalescent plasma donation (CPD) was satisfactory among participants. Knowledge showed positive correlation with the key motivations (r=0.0414, p= 0.000) and negative correlation with the barriers (r=-0.128, p=0.015). Conclusion: This study indicated that the knowledge of participants regarding convalescent plasma donation (CPD) was satisfactory. Knowledge had a positive impact on motivation for CPD. Barriers to convalescent plasma donation were more common among female participants. Barriers showed a negative correlation with key motivation and knowledge. Keywords: Barriers, Plasma, Donation.